An efficient off-axis multi-pass Nd:glass amplifier utilizing a birefringence crystal. (2nd October 2019) - Yao, Ke; Xie, Xudong; Tang, Jun; Fan, Chen; Gao, Song; Lu, Zhenhua; Fu, Xuejun; Tian, Xiaocheng; Zheng, Kuixing; Fan, Mengqiu; Zhu, Qihua
Abstract: In this paper we propose an efficient off-axis multi-pass Nd:glass amplifier with a birefringence crystal. By utilizing the optical principle of birefringence crystals and the angle differences of the input–output laser directions in a typical off-axis amplifier, the amplification-pass was extended from four-pass to eight-pass without increasing the off-axis angle. The detailed principles and amplifier parameter design are presented. Using the proposed off-axis eight-pass amplifier, a 1 Hz repetitive Nd:glass amplifier at several joules was experimentally demonstrated. A total transmission of 54% was achieved. At an input energy of 1.5 mJ and small-signal gain of 3.6, the output energy and the corresponding net gain were 2.5 J and 1667, respectively. The beam quality was good. The spatial intensity modulation index for 90% beam aperture was 1.29 and the 95% energy concentration of far field patterns was 2.77 times the diffraction limit.